PENGARUH KEMANDIRIAN BELAJAR SISWA DAN GAYA MENGAJAR GURU PAK TERHADAP PRESTASI BELAJAR SISWA DI SMP BETHEL JAKARTA - Tryastuti Wuryandari; Elyzabeth Dwi Vitoria Demetouw (Bethel Press, 2023)
This study aims to analyze the influence of students’ self-regulated learning and the teaching style of Christian Education (PAK) teachers on the academic achievement of junior high school students. A quantitative approach with a correlational design was employed. The research sample consisted of 120 students in grades VIII and IX, selected using proportional random sampling. Data on self-regulated learning and teaching style were collected through validated and reliable questionnaires, while students’ academic achievement was obtained from official semester report scores. Multiple linear regression analysis revealed that both independent variables had a positive and significant effect on academic achievement (R² = 0.298; p < 0.001), with teaching style contributing slightly more than self-regulated learning. These findings highlight the importance of synergy between students’ learning autonomy and the pedagogical quality of Christian Education teachers in enhancing academic outcomes and supporting the internalization of Christian values.